Electromagnetic Torque Analysis and Structure Optimization of Interior Permanent Magnet Synchronous Machine with Air-Gap Eccentricity - Jing Wang; Yubin Wang (Energies, 2023)
Interior permanent magnet synchronous machine with air-gap eccentricity (AGE-IPMSM) has the advantages of low torque ripple and low noise. However, air-gap eccentricity will lower the power density of the machine to a certain extent. In this paper, an 18-slot/8-pole interior permanent magnet synchronous machine with air-gap eccentricity is taken as the research object. According to the magnetic circuit method, the no-load and load air-gap magnetic field analytical models are calculated, respectively. Then, by Maxwell’s tensor method, the variation law of radial and tangential air-gap magnetic density harmonic amplitudes and phase angle difference cosine values are analyzed, and it is concluded that the electromagnetic torque can be improved by increasing phase angle difference cosine values of the magnetic density harmonic, which produces the driving torque after eccentricity. On this basis, in order to improve the output characteristics of the machine, the eccentricity and the angle between the V-type permanent magnets are optimized with the total harmonic distortion (THD), electromagnetic torque, and torque ripple as the optimization goals, and then the optimal structure size parameters of the machine are finally determined. Finally, a prototype is manufactured on the basis of the optimal parameters, and the experimental results of the prototype verify the validity and correctness of the theoretical analysis and finite element analysis (FEA).